Adsorptive removal of Lead from water by the effective and reusable magnetic cellulose nanocomposite beads entrapping activated bentonite. (20th October 2016) - Luo, Xiaogang; Lei, Xiaojuan; Xie, Xiuping; Yu, Bo; Cai, Ning; Yu, Faquan
Highlights: Combined cellulose and filler to create the renewable and biocompatible adsorbents. Cellulose used as matrix made the beads had macro- and nano-porous structure. Functional inorganic filler improve adsorption capacity and operational convenience. Beads had superior adsorption and desorption capabilities on lead. Development of cellulose-based sorbents for lead removal from water. Abstract: Many efforts have been driven to decontaminate the drinking water, and the development of efficient adsorbents with the advantages of cost-effectiveness and operating convenience for the removal of Pb 2+ from water is a major challenge. This work was aimed to explore the possibility of using cellulose-based adsorbents for efficient adsorption of Pb 2+ . The millimeter-scale magnetic cellulose-based nanocomposite beads were fabricated via an optimal extrusion dropping technology by blending cellulose with the carboxyl-functionalized magnetite nanoparticles and acid-activated bentonite in NaOH/urea aqueous solution, and then they had been tested to evaluate the effectiveness in the removal of Pb 2+ from water. The effects of contact time, initial heavy metal ion concentrations, adsorption isotherms and solution pH on the sorption behavior were studied. The thermodynamic parameters (Δ G, Δ H and Δ S ) indicated that the adsorption processes were feasible, spontaneous, endothermic and mainly controlled by chemical mechanisms. The reusability of the adsorbent was also studied.